2013
DOI: 10.1242/dev.087825
|View full text |Cite
|
Sign up to set email alerts
|

Sim1a and Arnt2 contribute to hypothalamo-spinal axon guidance by regulating Robo2 activity via a Robo3-dependent mechanism

Abstract: SUMMARYPrecise spatiotemporal control of axon guidance factor expression is a prerequisite for formation of functional neuronal connections. Although Netrin/Dcc-and Robo/Slit-mediated attractive and repulsive guidance of commissural axons have been extensively studied, little is known about mechanisms controlling mediolateral positioning of longitudinal axons in vertebrates. Here, we use a genetic approach in zebrafish embryos to study pathfinding mechanisms of dopaminergic and neuroendocrine longitudinal axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In a subset of zebrafish hypothalamic neurons that project to the hindbrain and spinal cord, the bHLH-PAS transcription factors Sim1a and Arnt2 regulate lateral position by downregulating Robo3 (Schweitzer et al, 2013 …”
Section: Transcriptional Control Of Lateral Position Through the Regumentioning
confidence: 99%
“…In a subset of zebrafish hypothalamic neurons that project to the hindbrain and spinal cord, the bHLH-PAS transcription factors Sim1a and Arnt2 regulate lateral position by downregulating Robo3 (Schweitzer et al, 2013 …”
Section: Transcriptional Control Of Lateral Position Through the Regumentioning
confidence: 99%
“…To date 7 studies have specifically investigated the role that Slit proteins, through their interaction with Robo receptors, play in the growth and guidance of dopaminergic neurites [10,11,12,13,14,15,16] (table 1); 2 of these studies, Lin et al [11] and Lin and Isacson [12], reported in vitro studies using primary cultures of the ventral midbrain of rats and murine embryonic stem (ES) cell-derived dopaminergic neurons, and 1 study has reported how Slit2 affects human ES cell-derived dopaminergic neurons in vitro [14]. The other 4 studies have investigated the role of Slits and Robos in the growth of longitudinal dopaminergic projections in vivo (mouse: [10,15] zebrafish: [13,16]).…”
Section: Figmentioning
confidence: 99%
“…The other 4 studies have investigated the role of Slits and Robos in the growth of longitudinal dopaminergic projections in vivo (mouse: [10,15] zebrafish: [13,16]). In addition, a recent study has also reported an increase in the number of tyrosine hydroxylase (TH, the rate-limiting enzyme for dopamine synthesis) immunoreactive (TH-ir) profiles in the adult zebrafish optic tectum in Robo2 astray mutants [17] (astray means ‘away from the correct path'; this is a mutant zebrafish line identified due to defects in their retinotectal pathfinding [18]).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations